THE ROLE OF FINANCIAL LITERACY IN ENSURING FINANCIAL BALANCE IN SMALLHOLDER FARMS (International Educators Conference, 2025)
This study evaluates the impact of financial literacy on the economic stability of smallholder farms. It explores the role of digital technologies, financial education, and access to credit in promoting resilience among smallholders. The necessity of implementing efficient financial management practices is substantiated through analytical and practical considerations. The findings contribute to the design of inclusive strategies for sustainable agricultural development in Uzbekistan.